Understanding the Impact of Incentive Policy and Social Attribute to Enhance the Consumers’ Purchase Intentions towards BEVs: TPB Explained - Syahputro, Pringgo; Dedi Abdul Hadi (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2024)
The government of Indonesia has its ambition to reduce carbon emissions as it is one of the largest emitters in the world. The number of four-wheeled vehicles is also estimated to increase as the economy grows rapidly. The action to deal with carbon emissions is to switch to renewable energy and electrification. In addition, Indonesia has a massive nickel reserve in the world. The government aims to not only reduce carbon emissions but also to attract big players in Battery Electric Vehicle (BEV) industry to invest in Indonesia. The study of BEVs adoption in Indonesia is still limited. It is essential to understand the consumer’s perception of incentive policies and social attributes to know which policies are better and why. Causal research was applied to test the hypotheses by using SEM-path analysis provided by AMOS. The study found that the strong predictors of purchase intentions towards BEVs are the perceptions of financial incentive and convenience policies, and attitudes towards BEVs. Indonesian consumer tends to do not consider environmental concerns and social norms. The novelty of this study is to incorporate perceived usefulness as a mediator. The respondents might not be actual BEV owners and have no experience using BEV. They also might not experience and understand some policies well. This study aims to provide information for the government as policy maker on which policies are better and why, in relation to enhance the consumers’ intention to purchase BEVs. keywords: financial incentive, tax, subsidy, electric vehicle, sustainability